Anaesthesia for Antenatal Diagnosed Duodenal Atresia with Undiagnosed Persistent Pulmonary Hypertension of Neonate - Yadav, Rupesh Kumar; Dhungel, Bidur Kumar; Hamal, Pawan Kumar; Pokhrel, Nabin; Shrestha, Manoj Kumar (Journal of Nepal Health Research Council, 2021)
Conversion of fetal circulation to adult-type occurs immediately after birth but neonates with problems in the development of pulmonary vasculature are prone to revert back to fetal circulation. This phenomenon is known as flip-flop circulation which may be induced perioperatively and as such anesthesiologist are central to its management. We report a case of term neonate planned for repair of duodenal atresia that despite having no respiratory symptom preoperatively developed severe hypoxemia under anesthesia that was even unresponsive to 100% oxygen. The intraoperative hemodynamics of the neonate was managed along with supportive care successfully. A postoperative echocardiogram confirmed the evidence of persistent pulmonary hypertension of the newborn.Keywords: Duodenal atresia; flip flop circulation; neonates; persistent pulmonary hypertension of newborn